ReguLA: A Self-Regulated Learning Component for Online Learning Systems - Ramos, Silas Augusto; Barros, Abílio Nogueira; Silva, Rafael de Amorim; Mangaroska, Katerina; Vesin, Boban; Mello, Rafael Ferreira (Anais do Workshop de Aplicações Práticas de Learning Analytics e Inteligência Artificial no Brasil (WAPLA), 2025)
This work describes the development of ReguLA, a technological component that encompasses Self-Regulated Learning (SRL) theory, aimed at empowering students to take an active role in their learning processes within online educational environments. SRL emphasizes the student as the protagonist by encouraging goal-setting, strategic monitoring, and reflective evaluation. Recognizing the challenges in applying SR particularly its voluntary adoption by learners ReguLA is designed to provide flexible support, allowing students to choose their level of engagement with self-regulatory practices. This approach fosters critical thinking and autonomy while respecting individual decision-making in learning. As a first phase, this study presents the theoretical foundations, the design of the components aligned with the SRL phases, and the prospects of integrating data mining techniques to refine personalized learning suggestions.